The Process of Interactions among Students of Different Cultures and Nationalities at a Malaysian Public University and Its Effects on Their Academic and Personal Lives - Abdul Qahar, Sarwari; Ainol Haryati, Ibrahim; Nor Ashikin, Abdul Aziz (IOSR-JHSS, 2014)
Daily interpersonal communication among students of different cultures and countries, and their personal and academic lives at the collegiate environments are among the important educational issues to be evaluated. Thus, this study aimed to assess the effects of daily interpersonal communication between local and international students of a Malaysian public university, University Malaysia Pahang (UMP) on their personal and academic lives. Findings of this research project may help the related policymakers and working-bodies at universities to improve communication and academic skills of students by increase of daily interaction opportunities among them. The quantitative survey with its 220 participants from both local and international students of UMP was applied as the main method of this study, and also qualitative interviews were conducted to enrich the data. According to the findings of this study, interactions between Malaysian and international students of UMP had positive effects on their personal and academic lives, and paved the ways for them to learn some essential communication skills, and also helped them to be happy, and have enough collaborative activities at the university campus. However, further studies may deepen the information on the related issues.